Gender Differences in Depressive Symptom Profile: Results from Nationwide General Population Surveys in Korea - Kim, Ji-Hyun (J Korean Med Sci, 2015)
This study investigated gender differences in symptom profiles of major depressive disorder (MDD) in the Korean general population. Data were pooled from the series of nationwide Korean Epidemiologic Catchment Area surveys conducted in 2001, 2006 and 2011, respectively. Of the 18,807 participants, 507 (397 women and 110 men) were diagnosed with MDD within the prior 12 months. In agreement with previous studies, women with MDD appeared to be more vulnerable to experiencing atypical depressive episodes defined as depression with two or more symptoms of fatigue, increased appetite and hypersomnia (P < 0.001). In terms of individual symptoms, female gender was significantly related with higher prevalence of fatigue (P = 0.008), hypersomnia (P = 0.001), noticeable psychomotor retardation (P = 0.029) and suicidal attempts (P = 0.016) with adjustment for birth cohort effect, partner status, and employment status. In the same analysis, men with MDD appeared more vulnerable to decreased libido than women (P = 0.009). This is the first report to demonstrate gender differences in symptomatology of MDD in the general Korean population, and the results are comparable to previous investigations from western societies. Assumingly, the intercultural similarity in female preponderance to atypical depression might reflect the common biological construct underlying the gender difference in mechanism of MDD. In clinical settings, gender differences of MDD should be carefully considered, because these features could be related with treatment response and drug side effects.